Analysis of Placement Conditions on Roads and Characteristics of Railway Crossings in the Republic of Kazakhstan - D. V. Kapskiy; E. N. Kot; S. V. Bogdanovich; A. G. Rybinskiy; K. Ibrayev (Наука и техника)
Road traffic accidents of vehicles with a rolling stock of railways lead to the most serious consequences. Many level crossings are places of long delays of vehicles both before and after the traffic. In this case and in many others, the intersections of highways with railways sharply limit the capacity of the highway. Level crossings require the utmost attention of the traffic organization, since they must include not only devices for the movement of cars, but also pedestrian and sidings. Despite the fact that the problem of road traffic accidents at level crossings is not new, research and analysis of statistics in this area continues around the world. The paper considers the level crossings on the Republican highways of the Republic of Kazakhstan. Research has been carried out on ways to improve traffic safety at such crossings. The situation at the level crossings of the roads of Republican significance, as well as possible restrictions and regulatory requirements, have been studied in the paper. The paper presents results of a detailed collection of data at the facilities, which will serve as the basis for the development of a detailed program for improving the regulatory and technical base of the road sector in Kazakhstan to improve the safety of  road transport infrastructure, taking into account existing standards. Recommendations are given for the implementation and generalization of advanced international experience in organizing road traffic at railway crossings, which will contribute to the adaptation of the Republic of Kazakhstan in the context of the development of transport and communications.